2020
DOI: 10.1038/s41598-020-72161-w
|View full text |Cite
|
Sign up to set email alerts
|

Safety and functional enrichment of gut microbiome in healthy subjects consuming a multi-strain fermented milk product: a randomised controlled trial

Abstract: Many clinical studies have evaluated the effect of probiotics, but only a few have assessed their dose effects on gut microbiota and host. We conducted a randomized, double-blind, controlled intervention clinical trial to assess the safety (primary endpoint) of and gut microbiota response (secondary endpoint) to the daily ingestion for 4 weeks of two doses (1 or 3 bottles/day) of a fermented milk product (Test) in 96 healthy adults. The Test product is a multi-strain fermented milk product, combining yogurt st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 62 publications
3
16
0
Order By: Relevance
“…Overall, the Test product affected gut microbiota mostly during the recovery phase following Hp treatment. Also, the Test product effect seemed more pronounced in the present study in case of microbiota alteration than in healthy subjects not exposed to antibiotics as previously reported [ 20 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Overall, the Test product affected gut microbiota mostly during the recovery phase following Hp treatment. Also, the Test product effect seemed more pronounced in the present study in case of microbiota alteration than in healthy subjects not exposed to antibiotics as previously reported [ 20 ].…”
Section: Discussionsupporting
confidence: 86%
“…A dairy product containing the strain Lacticaseibacillus paracasei ( Lp ) CNCM I-1518 was previously shown to reduce both antibiotic associated diarrhea (AAD) and Cd -associated diarrhea (CDAD) occurrence in hospitalized elderly [ 17 , 18 ] and to increase the Hp eradication rate in children [ 19 ]. Recently, a seven-strain fermented milk product containing Lp CNCM I-1518, Lp CNCM I-3689, Lacticaseibacillus rhamnosus ( Lr ) CNCM I-3690, and yogurt strains, was shown to be safe in healthy subjects [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lower colonization capacity (CFU/larvae) of Y. lipolytica 242 observed in Tg(Bacmpx:GFP) i114 , compared to D. hansenii 97, could explain their lower protection effect. This highlights the importance of the dose on probiotic effects, as recently reported (Alvarez et al, 2020). The dose must be adjusted not only considering the probiotic strain but also the host target and disease context.…”
Section: Discussionmentioning
confidence: 64%
“…The analysis of gut microbiota composition was performed using different methods, which were often applied in combination. Three studies analyzed microbiota variations through 16S rRNA based or whole genome shotgun metagenomics ( 44 , 47 , 48 ) allowing detection of all microbial groups, while qPCR was used to evaluate the presence of specific microbial groups ( 45 , 48 ). NGS was performed on V3–V4 ( n = 2) or V4–V5 ( n = 1) variable regions of the 16S rRNA gene.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, conflicting results were obtained at the level of gut bifidobacterial species, which were reported to increase ( 49 ), decrease ( 47 ), or remain unaffected ( 52 ). One study reported that, while gut microbiota structure was modestly modified after consumption, a few genera corresponding to Lactobacillus, Holdemania , and Clostridiales were differentially affected in response to different doses of ingested probiotic food ( 44 ). Finally, 2 studies reported no significant changes in the overall composition of gut microbiota following fermented milk ingestion ( 50 , 51 ).…”
Section: Resultsmentioning
confidence: 99%